Visual guideline for agile creation of IoT applications for LoRaWAN networks. (1st March 2021) - Amaya, Sebastian Yesid Tabares; Zafra, José Noé Poveda; Gaona-García, Elvis Eduardo
This paper presents the recommended guidelines for the creation of applications in LoRaWAN and IoT LP-WAN network technology. This work is based on the LoRa Alliance documentation and also from the different applications for the LoRaWAN network tested in Engineering Laboratories of Universidad Distrital Francisco José de Caldas. Since LoRaWAN is an open technology, an alternative to the suggested methods was development for a practical implementation of applications based on IoT protocols such as MQTT, following a flow-oriented programming paradigm. The main objective is to suggest the configuration and software units' requirements that must be considered for communication in the application layer.